2020
DOI: 10.1097/hjh.0000000000002502
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of ADIPOQ gene associated with cardiovascular disease risk factors in European adolescents: the Healthy Lifestyle in Europe by Nutrition in Adolescence study

Abstract: Objectives: Cardiovascular diseases (CVDs) are responsible of 31% of all deaths worldwide. Genetic predisposition to CVDs in adolescents remains largely unknown.Aims of present research are to examine the association of ADIPOQ gene polymorphisms with cardiovascular disease risk factors in European adolescents. Methods: A total of 14 polymorphisms in the ADIPOQ gene were genotyped in 1.057 European adolescents (12-18 years old) from the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross-Sectional Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These genes all have negative SLPs, suggesting that rare variants impacting their functioning might tend to be protective against hyperlipidaemia. ADIPOQ (SLP=-1.37) codes for adiponectin, an adipokine which is expressed in adipocytes which influences fat metabolism, and common variants in the gene are associated with cardiovascular disease risk and lipid levels (Liu et al, 2018;Salazar-Tortosa et al, 2020;Wang et al, 2019;Zhang et al, 2019). Adiponectin has a hypoglycaemic effect and can reverse the insulin resistance associated with both lipoatrophy and obesity (Berg et al, 2001;Yamauchi et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These genes all have negative SLPs, suggesting that rare variants impacting their functioning might tend to be protective against hyperlipidaemia. ADIPOQ (SLP=-1.37) codes for adiponectin, an adipokine which is expressed in adipocytes which influences fat metabolism, and common variants in the gene are associated with cardiovascular disease risk and lipid levels (Liu et al, 2018;Salazar-Tortosa et al, 2020;Wang et al, 2019;Zhang et al, 2019). Adiponectin has a hypoglycaemic effect and can reverse the insulin resistance associated with both lipoatrophy and obesity (Berg et al, 2001;Yamauchi et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This genetic variant of the ADIPOQ gene presents scarce studies in the literature, and these studies have reported contradictory results. For example, the Healthy Lifestyle in Europe by Nutrition in Adolescents Study [ 8 ] has shown a strong association between rs822393 polymorphism, HDL-cholesterol, and APoA1 serum levels. Moreover, in a noninterventional design [ 21 ], a lack of association between this single nucleotide variant (SNV) and metabolic parameters was observed.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in literature might be explained to the different ethnic groups or even the different ages of the patients (adolescents vs. adults), and finally, the presence of different allele frequencies and penetrance of this SNV in these populations. Moreover, this area of knowledge is of great interest because HDL-cholesterol has a clear relationship with cardiovascular events [ 22 ], and rs822393 variant is related with cardiovascular risk score, HDL-cholesterol, and systolic blood pressure [ 8 ], too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation